Comparative study of Coarse Aggregate Properties along the Longitudinal Sections of Kaligandaki River in Mustang (Universal Technical Journal of Lumbini International Academy of Science and Technology, 2025)
The most significant component of concrete is aggregate. The demand for aggregates is quite high in Nepal's construction sector for road construction and concrete works. River-borne aggregate material still meets a large portion of the need. The Kaligandaki river is one of most prominent among others for extraction of riverbed material in Gandaki Provine and it is the most economic supplier for aggregates in Mustang district. The quantity of sediments attracts construction stakeholders for use of locally available materials. This study's goal was to analyse the properties of aggregates and variation in aggregate strength at a particular stretch of the Kaligandaki river basin in Mustang district. On the basis of accessibility and deposition, representative samples were taken for study purposes from five carefully chosen riverbank locations. Lab tests for physical properties (FM, specific gravity, water absorption, combined FI and EI) and mechanical properties (LAA, AIV and ACV) were conducted on the samples to evaluate their quality and strength for the construction works. Suitability of aggregates based on strength assessment samples was assured by compliance test to limits specified in DOR specification.FM, specific gravity, water absorption, combined FI and EI were found in range of (6.57-7.05), (2.62-2.71), (0.485-0.723)% and (33.14-42.29)% respectively. It was concluded that aggregates from all the sources are suitable in their hardness, toughness and compressive strength. A linear relationship between the combined flakiness and elongation index, LAA, AIV and ACV values with longitudinal variation of Kaligandaki river was established.